Factors Associated With the Dilation of Perivascular Space in Healthy Elderly Subjects - Huang, Peiyu; Zhu, Zili; Zhang, Ruiting; Wu, Xiao; Jiaerken, Yeerfan; Wang, Shuyue; Yu, Wenke; Hong, Hui; Lian, Chunfeng; Li, Kaicheng; Zeng, Qingze; Luo, Xiao; et al. (Frontiers in Aging Neuroscience, 2021)
Background: The dilation of perivascular space (PVS) has been widely used to reflect brain degeneration in clinical brain imaging studies. However, PVS characteristics exhibit large differences in healthy subjects. Such variations need to be better addressed before PVS can be used to reflect pathological changes. In the present study, we aim to investigate the potential influence of several related factors on PVS dilation in healthy elderly subjects. Methods: One-hundred and three subjects (mean age = 59.5) were retrospectively included from a prospectively collected community cohort. Multi-modal high-resolution magnetic resonance imaging and cognitive assessments were performed on each subject. Machine-learning based segmentation methods were employed to quantify PVS volume and white matter hyperintensity (WMH) volume. Multiple regression analysis was performed to reveal the influence of demographic factors, vascular risk factors, intracranial volume (ICV), major brain artery diameters, and brain atrophy on PVS dilation. Results: Multiple regression analysis showed that age was positively associated with the basal ganglia (BG) (standardized beta = 0.227, p = 0.027) and deep white matter (standardized beta = 0.220, p = 0.029) PVS volume. Hypertension was positively associated with deep white matter PVS volume (standardized beta = 0.234, p = 0.017). Furthermore, we found that ICV was strongly associated with the deep white matter PVS volume (standardized beta = 0.354, p < 0.001) while the intracranial artery diameter was negatively associated with the deep white matter PVS volume (standardized beta = −0.213, p = 0.032). Conclusions: Intracranial volume has significant influence on deep white matter PVS volume. Future studies on PVS dilation should include ICV as an important covariate.